Calculation Method of Allowable Continuous Current for Direct Burial Laying HVDC Underground Cable - Kyu-hoon Park; Il Kwon; Bang-wook Lee (Energies, 2021)
The calculation of the continuous allowable current of an underground cable is determined by various characteristics. To calculate the allowable current in cables with alternating magnetic fields such as AC, special phenomena such as the proximity effect and skin effect must be applied. However, there are no standards or research related to the calculation of the continuous allowable current of a DC power cable that does not have an alternating magnetic field. In this paper, a quantitative DC cable continuous allowable current calculation formula of direct burial laying was derived by applying the existing AC cable continuous allowable current calculation method to the DC system. We developed a calculation tool that can calculate the continuous allowable current of DC cables using the derived formula. Assuming the cable conditions (cable specification, laying conditions, soil characteristics, arrangement, and number of strands, etc.), a continuous allowable current simulation of DC cables was performed. In addition, the level of contribution to the continuous allowable current value was analyzed by classifying the parameter categories into major and minor factors in the order of influence on the allowable current among the determined calculated parameters. As a result, the effectiveness of the DC cable continuous allowable current calculation tool derived by performing the allowable current calculation simulation was evaluated, and the allowable current calculation method of the HVDC cable was established.